Valorization of sugarcane bagasse through biofuel and value-added soluble metabolites production: Optimization of alkaline hydrothermal pretreatment. (October 2022) - Soares, Laís A.; Solano, Magnólia G.; Lindeboom, Ralph E.F.; van Lier, Jules B.; Silva, Edson L.; Varesche, Maria B.A.
Abstract: Sugarcane bagasse (SCB) is increasingly considered as a potential source for bioenergy or bulk chemicals production. However, efficient pretreatment techniques need to be developed to make full use of its potential. A central composite design was employed to evaluate the effect of temperature (146.4–213.6 °C), NaOH concentration (0.7–2.3 M) and treatment time (3.2–36.8 min) on the hydrothermal pretreatment of SCB. Glucose was the abundant fermentable sugar released in the hydrolysate (4.0 g/L) and its concentration was significantly (p-value < 0.05) affected by temperature and NaOH concentration. Sugars released in the hydrolysate and the remaining cellulose, hemicellulose, and lignin in the pretreated fiber were anaerobically co-digested in batch thermophilic assays (55 °C). Propionate, one of the most promising platform chemicals, was the main metabolite produced (0.5 g/L) and its concentration was significantly affected by temperature and NaOH concentration. Both NaOH concentration and pretreatment duration significantly affected methane composition in the biogas (p-value <0.05 and 0, 10 respectively). Defluviitoga, and Methanothermobacter genera were favored in response to alkaline hydrothermal pretreatment at the central point conditions (180 °C, 1.5 M NaOH, 20 min). Graphical abstract: Image 1 Highlights: Experimental design optimizing NaOH/hydrothermal pretreated sugarcane bagasse (SCB). Propionate was the main metabolite produced from NaOH/hydrothermal pretreated SCB. Methane optimization using solid/liquid product of pretreated SCB has been achieved. Defluviitoga and Methanothermobacter were favored by NaOH/hydrothermal pretreated SCB. Alkaline pretreated SCB exhibited potential for commodities chemicals production.